Problematizing as "Doing Physics": The importance of articulating, refining, and motivating problems in classrooms - Phillips, Anna. (Tufts University. Tisch Library., 2019)
Literature in science education positions questions as the launching point for scientific inquiry, and widely used standards, such as the Next Generation Science Standards often state: "Science begins with a question" (NGSS Lead States, 2013). Questions have generally been studied for their role in sparking student inquiry or helping students develop explanations or models, rather than as outcomes of important scientific work. Yet in professional science, we see many of the key insights behind scientific advancements takes place before there is a clear question or articulated problem. Constructing problems is itself a difficult task, and a clear problem is an achievement. In this dissertation, I examine the importance of turning feelings of uncertainty or unease into problems and motivating others to take up those problems, work I refer to as problematizing. I discuss several examples from the history of physics and draw upon writings of those who study physics and science more broadly to demonstrate the importance of problematizing in physics. I describe how problems in physics are gaps or inconsistencies across our perceptions of the world- information gathered via experiments and observation-our conceptions of the world-our models, theories, and principles-and our epistemic aims and values. I then show that students can engage in this important work, by looking at case studies of students doing science from the elementary level to the undergraduate level. Next, I argue that the work of problematizing is not reflected in the Next Generation Science Standards, and propose changes for future standards to better reflect problematizing. I conclude with a discussion of future work that will lead to insights into how to promote problematizing in classrooms.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Physics.; Advisor: David Hammer.; Committee: Catherine Crouch, Kristen Wendell, and Roger Tobin.; Keywords: Physics, Education, and Philosophy of science.